WOMEN’S PERCEIVED HELPFULNESS OF POLICE AND SHELTER HOMES AND THEIR TOLERANCE TOWARDS MALE VIOLENCE IN FAMILIES - Saeed Ahmad Watto; Ambreen Naz; Ghulam Murtaza; Sobia Rashid (European Scientific Journal, ESJ, 2012)
This study has examined the differential influence of women’s perceived helpfulness of police and shelter homes on their varying duration of tolerating male violence in families. Accordingly, the attempts of women victims for seeking help were considered as one of the coping strategies with intimate violence. Accordingly: i) women’s styles of coping with intimate partner violence may influence their initiatives for adopting formal and informal resources of help-seeking; and ii) women may have varying perceptions of helpfulness of help-seeking resources in terms of what works and what does not work for countering intimate violence. Data was collected by interviewing all the women victims of domestic violence (n=154) who were the residents of two shelter homes namely: Dar-ul-Amaan; and Dastak situated in Lahore City. The results of Chi-square test showed a significant association between the levels of women’s perceived helpfulness of police, and the duration of their tolerance towards male domestic violence. Varying level of women’s perceived helpfulness of shelter homes had no significant influence on their changing duration of tolerating male domestic violence. However, of the respondents having varying level of perceived helpfulness of shelter homes a relative majority of them kept on tolerating male domestic violence for more than five years till getting refuge in shelter homes. It indicated that despite women differently perceived helpfulness of shelter homes they kept on bearing out the odds of male domestic violence for a longer period of time and preferred to stay with their abusers.